OPTIMIZATION OF MARBLE DUST AND BRICK POWDER IN CEMENT MORTAR FOR SUSTAINABLE CONSTRUCTION: A STRENGTH PERFORMANCE ANALYSIS - Er. Ravneet Singh Sidhu; Er. Anish Tayal; Er. Sandeep Maan (International Educational Journal of Science and Engineering, 2026)
The present research focuses on developing a sustainable cement mortar by incorporating marble dust and brick powder as partial replacement materials for cement and fine aggregate. Different mix combinations were prepared with varying replacement levels, and their mechanical performance was assessed through compressive strength tests conducted at 14 and 28 days. The findings reveal that controlled replacement levels contribute to improved strength performance, with optimum results achieved at 10% marble dust and combined 20% replacement levels. The improvement in strength is mainly associated with better particle packing and reduced internal voids within the mortar matrix. However, higher replacement percentages showed a decline in strength due to increased porosity and weaker interfacial bonding. The study also highlights the potential utilization of industrial waste materials in reducing environmental burden and conserving natural resources. The outcomes of this research provide a practical basis for selecting suitable replacement levels in mortar production while maintaining structural efficiency. Further investigation is required to evaluate long-term durability and large-scale application of such materials.